Multimodality Imaging Strategies for the Assessment of Aortic Stenosis: Viewpoint of the Heart Valve Clinic International Database (HAVEC) Group. (February 2016) - Dulgheru, Raluca; Pibarot, Philippe; Sengupta, Partho P.; Piérard, Luc A.; Rosenhek, Raphael; Magne, Julien; Donal, Erwan; Bernard, Anne; Fattouch, Khalil; Cosyns, Bernard; Vannan, Mani; Gillam, Linda; et al.
Abstract : Aortic stenosis is the most frequent valvular heart disease. In aortic stenosis, therapeutic decision essentially depends on symptomatic status, stenosis severity, and status of left ventricular systolic function. Surgical aortic valve replacement or transcatheter aortic valve implantation is the sole effective therapy in symptomatic patients with severe aortic stenosis, whereas the management of asymptomatic patients remains controversial and is mainly based on individual risk stratification. Imaging is fundamental for the initial diagnostic work-up, follow-up, and selection of the optimal timing and type of intervention. The present review provides specific recommendations for utilization of multimodality imaging to optimize risk stratification and therapeutic decision-making processes in aortic stenosis. Abstract : Supplemental Digital Content is available in the text.